2012
DOI: 10.1021/es300901h
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Effects of Cu Metalloprotein-Driven Silver Nanoparticle Dissolution

Abstract: Interactions of a model Cu-metalloprotein, azurin, with 10-100 nm silver nanoparticles (NPs) were examined to elucidate the role of oxidative dissolution and protein interaction on the biological reactivity of NPs. Although minimal protein and NP structural changes were observed upon interaction, displacement of Cu(II) and formation of Ag(I) azurin species under aerobic conditions implicates Cu(II) azurin as a catalyst of NP oxidative dissolution. Consistent with NP oxidation potentials, largest concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 45 publications
3
37
0
1
Order By: Relevance
“…Once the NP or related transformed species interact with a physiologically active site on the cell surface, they may affect the cell metabolism and disrupt the cellular homeostasis [35]. If the interaction is strong enough to overwhelm the stress responses, which arise due to a disruption in homeostasis, a toxic outcome will ensue [36]. The bioavailability of a NP can be inferred by characterizing a biological end-point; these biological end-points will be different for different organisms (e.g., algae, bacteria, and fish) and may include metal bioaccumulation (sorption or uptake), photosynthetic activity, motility, respiration and growth [35].…”
Section: Mechanistic Considerations Of the Potential Toxic Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Once the NP or related transformed species interact with a physiologically active site on the cell surface, they may affect the cell metabolism and disrupt the cellular homeostasis [35]. If the interaction is strong enough to overwhelm the stress responses, which arise due to a disruption in homeostasis, a toxic outcome will ensue [36]. The bioavailability of a NP can be inferred by characterizing a biological end-point; these biological end-points will be different for different organisms (e.g., algae, bacteria, and fish) and may include metal bioaccumulation (sorption or uptake), photosynthetic activity, motility, respiration and growth [35].…”
Section: Mechanistic Considerations Of the Potential Toxic Actionmentioning
confidence: 99%
“…Algal cells are surrounded by cell walls, which are an important barrier to the physical penetration of ENMs into the cells [36]. Indeed, the importance of the cell wall in protecting the algal cells from Ag NP internalization has been demonstrated by Piccapietra et al [39], as they have found higher rate of Ag internalization in the cell-wall-free strain of C. reinhardtii as compared to the wild-type strain.…”
Section: Algae Related Considerations In Enm-cell Interactionmentioning
confidence: 99%
See 3 more Smart Citations